Composite battery diaphragm, preparation method thereof and lithium ion battery

By using a composite coating of zeolite imidazole frame material and organic-inorganic crosslinked gel precursor nanoparticles on the lithium-ion battery separator, the problem of degradation of lithium-ion batteries in low temperature environments is solved, and a higher Ion conduction and heat resistance improve the low-temperature performance of the battery.

CN119481583APending Publication Date: 2025-02-18HU ZHOU YAO NING GU TAI DIAN CHI YAN JIU YUAN YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411724882.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Lithium-ion batteries exhibit capacity attenuation, increased internal resistance and reduced charge and discharge efficiency in low temperature environments, mainly due to slowing electrochemical reaction speed and changes in physical properties of electrode materials and electrolytes.

Method used

A composite battery separator is used, which consists of 30~60% zeolite imidazole frame material, 20~50% organic-inorganic crosslinked gel precursor nanoparticles, 3~30% aqueous binder and 1~10 % dispersant is composed of and coated on the diaphragm base film by spraying or rolling to form a composite coating with high ion conductivity and high adhesion.

Benefits of technology

Through the combination of zeolite imidazole frame material and organic-inorganic crosslinked gel precursor nanoparticles, the ion conduction ability and heat resistance of the composite coating are enhanced, and the capacity maintenance of lithium-ion batteries under low temperature conditions is improved. rate and charge and discharge performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481583A_ABST
    Figure CN119481583A_ABST
Patent Text Reader

Abstract

The invention discloses a composite battery diaphragm, a preparation method thereof and a lithium ion battery, the composite battery diaphragm comprises a diaphragm base membrane and a composite coating coated on at least one side of the diaphragm base membrane; the composite coating comprises the following components: 30%-60% of a zeolite imidazolate framework material, 20%-50% of organic-inorganic cross-linked gel precursor nanoparticles, 3%-30% of a water-based binder and 1%-10% of a dispersing agent. According to the invention, the high ion conduction performance and high adhesion of the battery diaphragm can be improved, so that the lithium ion battery manufactured by adopting the battery diaphragm disclosed by the invention has better low-temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite battery separator and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have gradually become one of the most popular energy storage devices due to their high energy density, long cycle and good charge and discharge efficiency. However, the performance of lithium-ion batteries will significantly decline in low temperature environments, which is manifested as capacity decay, increased internal resistance and reduced charge and discharge efficiency. This is mainly due to the slowdown of the electrochemical reaction inside the battery and the change in the physical properties of the electrode materials and electrolytes. In order to solve these problems, industry insiders have been committed to exploring ways to improve the low-temperature performance of lithium-ion batteries.

[0003] Among the components of lithium-ion batteries, the battery separator is a key component of the battery. While preventing the positive and negative electrodes from contacting and allowing ion conduction, the conduction rate of the battery separator and its wettability with the electrolyte will affect the low-temperature performance of the battery. In order to improve the low-temperature performance of the battery, in addition to improving the pore structure of the separator substrate to increase the ion conduction channel and speed, the battery separator can also be optimized by coating to improve the battery's charge and discharge performance.

[0004] Existing diaphragm coatings are mainly divided into two categories: inorganic coatings and organic coatings. Among them, inorganic coatings mostly use alumina, boehmite, etc., and inorganic particles are prone to accumulation and clogging of the diaphragm pores during coating, affecting the charge and discharge performance of the battery. Organic coatings mostly use polymer materials such as polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA) and aramid. Although they can solve the problem of inorganic particle accumulation, they will also cause the ionic conductivity of the diaphragm to decrease, thereby affecting the charge and discharge performance of the battery. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings, the object of the present invention is to provide a composite battery separator and a preparation method thereof and a lithium-ion battery, wherein the composite battery separator can have both high ion conductivity and high adhesion, thereby improving the low-temperature performance of the lithium-ion battery.

[0006] In order to achieve the above purpose, one of the technical solutions adopted by the present invention is: a composite battery separator, comprising a separator base film and a composite coating coated on at least one side of the separator base film; the composite coating comprises the following components: 30~60% of zeolite imidazolate framework material, 20~50% of organic-inorganic cross-linked gel precursor nanoparticles, 3~30% of aqueous binder, and 1~10% of dispersant.

[0007] The beneficial effects of the composite battery separator of the present invention are: By compounding zeolite imidazolate framework materials with organic-inorganic cross-linked gel precursor nanoparticles, the high specific surface area and porous structure of the zeolite imidazolate framework materials can be utilized to enhance the ion conductivity and heat resistance of the composite coating; at the same time, the organic-inorganic cross-linked gel precursor nanoparticles can improve the solubility of high-temperature resistant polymers in electrolytes, so that the organic-inorganic cross-linked gel precursor nanoparticles are in situ polymerized under the initiation of lithium salts in the electrolyte to form a three-dimensional network organic-inorganic cross-linked gel layer, which is beneficial to bonding the positive electrode, the separator, and the negative electrode together under low temperature conditions, thereby improving the low-temperature performance of lithium-ion batteries.

[0008] Furthermore, the organic-inorganic cross-linked gel precursor nanoparticles include vinyl functionalized inorganic nanoparticles, a first monomer, a second monomer, a third monomer, an initiator, an emulsifier and a solvent, wherein the first monomer is an acrylate or allyl carbonate monomer, the second monomer is a maleimide monomer, and the third monomer is an olefin epoxy or olefin oxygen-containing heterocyclic monomer.

[0009] In the organic-inorganic cross-linked gel precursor nanoparticles, by introducing vinyl functionalized inorganic nanoparticles, the softening temperature of the gel polymer can be increased, thereby increasing the thermal shrinkage temperature and reducing the thermal elongation rate. The first monomer adopts an olefin monomer with high solubility in the electrolyte, the second monomer adopts a high temperature resistant olefin monomer, and the third monomer adopts an olefin monomer that can be polymerized by lithium salt. The organic-inorganic cross-linked gel precursor nanoparticles prepared by multi-monomer copolymerization can improve their solubility in the electrolyte when applied to lithium battery separators, so as to solve the problem that high temperature resistant polymers are difficult to apply to separator adhesives due to their insolubility.

[0010] Specifically, the organic-inorganic cross-linked gel precursor nanoparticles are prepared by the following steps: vinyl functionalized inorganic nanoparticles, a first monomer, a second monomer, a third monomer, an initiator and an emulsifier are uniformly mixed and dispersed in a solvent to form an emulsion system, and emulsion polymerization is performed by heating and stirring to obtain organic-inorganic cross-linked gel precursor nanoparticles.

[0011] Furthermore, the solid content of the vinyl functionalized inorganic nanoparticles in the emulsion system is 5-20%, the first monomer accounts for 1-20% of the mass content of the vinyl functionalized inorganic nanoparticles, the second monomer accounts for 1-20% of the mass content of the vinyl functionalized inorganic nanoparticles, the third monomer accounts for 1-20% of the mass content of the vinyl functionalized inorganic nanoparticles, the initiator accounts for 0.01-0.5 mol% of the total molar amount of the first monomer, the second monomer, and the third monomer, and the mass of the emulsifier accounts for 1-4% of the total mass of the vinyl functionalized inorganic nanoparticles, the first monomer, the second monomer, and the third monomer.

[0012] Furthermore, the vinyl-functionalized inorganic nanoparticles are one or more of vinyl-functionalized lithium germanium aluminum phosphate, vinyl-functionalized lithium lanthanum zirconium oxide, vinyl-functionalized lithium lanthanum zirconium tantalum oxide, vinyl-functionalized lithium lanthanum tantalum oxide, vinyl-functionalized lithium aluminum titanium phosphate, vinyl-functionalized alumina, vinyl-functionalized silica, and vinyl-functionalized boehmite, preferably vinyl-functionalized lithium aluminum titanium phosphate, vinyl-functionalized alumina nanoparticles, vinyl-functionalized lithium germanium aluminum phosphate, or vinyl-functionalized silica.

[0013] In the first monomer, the acrylate monomer is at least one of methyl acrylate, ethyl acrylate, hexyl acrylate, butyl acrylate, octyl acrylate, methyl methacrylate, ethyl methacrylate, hexyl methacrylate, octyl methacrylate, and ethoxyethyl acrylate, preferably methyl methacrylate or ethyl acrylate. The allyl carbonate monomer is at least one of allyl methyl carbonate, allyl phenyl carbonate, and allyl ethyl carbonate, preferably allyl methyl carbonate.

[0014] In the second monomer, the maleimide monomer is one or more of N-(4-aminophenyl)maleimide, N-(2-chlorophenyl)-maleimide, N-(4-fluorophenyl)maleimide, N-phenylmaleimide, N-(1-pyrene)maleimide, N-(o-tolyl)maleimide, N-(4-methyl-3-chlorophenyl)maleimide, and N-(2,4,6-trichlorophenyl)maleimide, preferably N-(2-chlorophenyl)-maleimide or N-phenylmaleimide.

[0015] In the third monomer, the olefin epoxy monomer or allyl carbonate monomer is one or more of propyl glycidyl ether, linoleic acid glycidyl ester-d5, methacrylate glycidyl ester, acrylate glycidyl ester, preferably allyl glycidyl ether.

[0016] The initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dodecyl peroxide, and diisopropyl peroxydicarbonate, preferably azobisisobutyronitrile or diisopropyl peroxydicarbonate.

[0017] The emulsifier is an anionic surfactant, an amphoteric surfactant or a nonionic surfactant.

[0018] The solvent is water, an alcohol solvent or a mixed solvent of the two, preferably water.

[0019] Furthermore, the zeolite imidazolate framework material (ZIFs) is selected from at least one of ZIF-8, ZIF-67, and MOF-5. Furthermore, the D 50 The particle size is 0.5~1μm.

[0020] Furthermore, the aqueous binder is selected from at least one of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), and carboxymethyl cellulose (CMC). Furthermore, the dispersant is selected from at least one of benzalkonium chloride, polydimethylguanidine salt, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium fatty alcohol polyvinyl ether sulfate, polysorbate, sorbitan fatty acid ester, alkyl glycoside, and alkylphenol polyoxyethylene ether.

[0021] The second technical solution adopted by the present invention is: a method for preparing a composite battery separator, comprising the following steps: (1) Preparation of organic-inorganic cross-linked gel precursor nanoparticles; (2) dispersing the zeolite imidazolate framework material, the organic-inorganic cross-linked gel precursor nanoparticles, the aqueous binder, and the dispersant in water to prepare an aqueous slurry; (3) The aqueous slurry is coated on at least one side of the separator base film by spraying or rolling, and then heated and dried to obtain a composite battery separator.

[0022] Furthermore, in step (3), the coating surface density of the aqueous slurry is 1-10 g / m 2 .

[0023] Furthermore, in step (3), the heating and drying temperature is 30-100° C., and the heating and drying time is 1-12 min.

[0024] The third technical solution adopted by the present invention is: a lithium-ion battery, comprising any of the composite battery separators described above. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 Schematic diagram of the capacity retention rate test at low temperature in a comparative experiment of an embodiment of the present invention. DETAILED DESCRIPTION

[0025] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more explicit definition of the protection scope of the present invention. It should be noted that the following embodiments are for a better understanding of the present invention, are not limited to the best embodiments, and do not limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0026] It should be noted that, in the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0027] In addition, if the specific experimental steps or conditions are not specified in the examples, the operations or conditions of the conventional experimental steps described in the literature in the art can be carried out. The numerical ranges shown by "~" in the examples indicate the ranges containing the values ​​recorded before and after "~" as the minimum and maximum values, respectively. If the manufacturers of the reagents or instruments are not specified, they are all conventional reagent products that can be obtained commercially.

[0028] Example 1 The organic-inorganic crosslinked gel precursor nanoparticles were prepared as follows: (1) Raw material composition: vinyl functionalized alumina nanoparticles, methyl methacrylate, N-(2-chlorophenyl)-maleimide, allyl glycidyl ether, azobisisobutyronitrile, sorbitan trioleate and water; (2) Vinyl functionalized alumina nanoparticles, methyl methacrylate, N-(2-chlorophenyl)-maleimide, allyl glycidyl ether, azobisisobutyronitrile, and sorbitan trioleate are uniformly dispersed in water to form an emulsion system, and stirred at a temperature of 60°C and a rotation speed of 1000 rpm to obtain organic-inorganic cross-linked gel precursor nanoparticles.

[0029] Among them, the solid content of vinyl functionalized alumina nanoparticles in the emulsion system is 20%, methyl methacrylate accounts for 20% of the mass content of vinyl functionalized alumina nanoparticles, N-(2-chlorophenyl)-maleimide accounts for 20% of the mass content of vinyl functionalized alumina nanoparticles, allyl glycidyl ether accounts for 20% of the mass content of vinyl functionalized alumina nanoparticles, azobisisobutyronitrile accounts for 0.5 mol% of the total molar sum of methyl methacrylate, N-(2-chlorophenyl)-maleimide and allyl glycidyl ether, and sorbitan trioleate accounts for 2% of the total mass of vinyl functionalized alumina nanoparticles, methyl methacrylate, N-(2-chlorophenyl)-maleimide and allyl glycidyl ether.

[0030] Example 2 The composite battery separator was prepared as follows: (1) preparing organic-inorganic crosslinked gel precursor nanoparticles according to Example 1; (2) Dispersing a zeolite imidazolate framework material, organic-inorganic cross-linked gel precursor nanoparticles, an aqueous binder and a dispersant in water to prepare an aqueous slurry; wherein the mass ratio of the zeolite imidazolate framework material, the organic-inorganic cross-linked gel precursor nanoparticles, the aqueous binder and the dispersant is 45:35:15:6, the zeolite imidazolate framework material is ZIF-8, the aqueous binder is PVDF, and the dispersant is sodium dodecyl sulfate.

[0031] (3) The aqueous slurry prepared in step (2) is coated on both sides of the separator base film by roller pressing, and the coating thickness reaches 2 μm; and the mixture is dried at 70° C. for 10 min to obtain a composite battery separator.

[0032] Example 3 The difference between this embodiment and embodiment 2 is that the mass ratio of the zeolite imidazolate framework material, the organic-inorganic cross-linked gel precursor nanoparticles, the aqueous binder and the dispersant is 30:50:3:3.

[0033] Example 4 The difference between this embodiment and embodiment 2 is that the mass ratio of the zeolite imidazolate framework material, the organic-inorganic cross-linked gel precursor nanoparticles, the aqueous binder and the dispersant is 60:20:30:10.

[0034] Example 5 The difference between this embodiment and embodiment 2 is that the zeolite imidazolate framework material is ZIF-67.

[0035] Example 6 The difference between this embodiment and embodiment 2 is that the zeolite imidazolate framework material is MOF-5.

[0036] Example 7 The difference between this embodiment and embodiment 2 is that the water-based binder is PVA.

[0037] Example 8 The difference between this embodiment and embodiment 2 is that the water-based binder is CMC.

[0038] Comparative Example 1 The difference between this comparative example and Example 2 is that the mass ratio of the zeolite imidazolate framework material, the organic-inorganic cross-linked gel precursor nanoparticles, the aqueous binder and the dispersant is 20:35:15:6.

[0039] Comparative Example 2 The difference between this comparative example and Example 2 is that the mass ratio of the zeolite imidazolate framework material, the organic-inorganic cross-linked gel precursor nanoparticles, the aqueous binder and the dispersant is 80:35:15:6.

[0040] Comparative Example 3 The difference between this comparative example and Example 2 is that the mass ratio of the zeolite imidazolate framework material, the organic-inorganic cross-linked gel precursor nanoparticles, the aqueous binder and the dispersant is 45:10:15:6.

[0041] Comparative Example 4 The difference between this comparative example and Example 2 is that the mass ratio of the zeolite imidazolate framework material, the organic-inorganic cross-linked gel precursor nanoparticles, the aqueous binder and the dispersant is 45:60:15:6.

[0042] Comparative Example 5 The difference between this comparative example and Example 2 is that: no zeolite imidazolate framework material is added, and the mass ratio of organic-inorganic cross-linked gel precursor nanoparticles, aqueous binder and dispersant is 75:15:6.

[0043] Comparative Example 6 The difference between this comparative example and Example 2 is that no organic-inorganic cross-linked gel precursor nanoparticles are added, and the mass ratio of the zeolite imidazolate framework material, the aqueous binder and the dispersant is 75:15:6.

[0044] Comparative Example 7 The difference between this comparative example and Example 2 is that the organic-inorganic cross-linked gel precursor nanoparticles are replaced by acrylic polymer particles.

[0045] Comparative Example 8 The composite battery separator was prepared as follows: (1) dispersing vinyl functionalized alumina nanoparticles, methyl methacrylate, N-(2-chlorophenyl)-maleimide, allyl glycidyl ether, azobisisobutyronitrile, sorbitan trioleate, ZIF-8, aqueous PVDF, and sodium dodecyl sulfate in water according to the component ratio of Example 2 to prepare an aqueous slurry; (2) The aqueous slurry prepared in step (1) is coated on both sides of the separator base film by roller pressing, and the coating thickness reaches 2 μm; and the mixture is dried at 70° C. for 10 min to obtain a composite battery separator.

[0046] Experimental example A lithium-ion battery comprises a battery cell electrode group and an electrolyte, wherein the battery cell electrode group comprises a positive electrode sheet, a negative electrode sheet and a separator disposed between the positive electrode sheet and the negative electrode sheet, and the separator is a composite battery separator prepared in Examples 2-8 and Comparative Examples 1-8. The preparation method of the lithium-ion battery is as follows: (1) The cell separator, negative electrode sheet and positive electrode sheet are stacked into an electrode group in the form of a laminate, and the electrode group is cold pressed using a hot press at a temperature of 25°C and a surface pressure of 2MPa to complete the production of the electrode group; (2) The prepared electrode group is packaged in a soft-pack form, and then the electrolyte is injected (the electrolyte is a mixture of EC, FEC, EMC, DEC, LiPF6, DTD, and LiPO2F2 in a mass ratio of 15:5.5:44:18:15:2:0.5), and a lithium-ion battery is obtained after pre-charging and formation.

[0047] The prepared lithium-ion battery was subjected to performance tests, and the test results are shown in Table 1.

[0048] Table 1 Test results of Examples 2-8 and Comparative Examples 1-8

[0049] According to Table 1, we can see that: (1) It can be seen from the test results of Examples 2-8 that the impedance of the composite battery separator prepared by the present invention is relatively small, indicating that the ion transmission inside the battery is faster; and the battery capacity can be maintained at more than 40% at a low temperature of -10°C; in addition, Example 2 uses ZIF-8 as the zeolite imidazolate framework material and PVDF as the aqueous binder, and the mass ratio of the zeolite imidazolate framework material, organic-inorganic cross-linked gel precursor nanoparticles, aqueous binder and dispersant is 45:35:15:6, and its adhesion, impedance and capacity retention rate at -10°C are the best.

[0050] (2) It can be seen from the test results of Comparative Examples 1-2 and Example 2 that when the ratio of the zeolite imidazolate framework material exceeds the ratio range of the present invention (30-60%), the impedance of the lithium-ion battery and the capacity retention rate at -10°C are poor.

[0051] (3) It can be seen from the test results of Comparative Examples 3-4 and Example 2 that when the ratio of the organic-inorganic cross-linked gel precursor nanoparticles exceeds the proportion range of the present invention (20-50%), the impedance of the lithium-ion battery and the capacity retention rate at -10°C are poor.

[0052] (4) From the test results of Comparative Example 5 and Example 2, it can be seen that the addition of zeolite imidazolate framework material can significantly improve the impedance of lithium-ion batteries and the capacity retention rate at -10°C.

[0053] (5) From the test results of Comparative Example 6 and Example 2, it can be seen that the addition of organic-inorganic cross-linked gel precursor nanoparticles can significantly improve the adhesion, impedance and capacity retention rate of lithium-ion batteries at -10°C.

[0054] (6) It can be seen from the test results of Comparative Example 7 and Example 2 that, compared with acrylic polymers, the lithium-ion battery prepared using organic-inorganic cross-linked gel precursor nanoparticles has better adhesion, impedance and capacity retention at -10°C.

[0055] (7) From the test results of Comparative Example 8 and Example 2, it can be seen that the lithium-ion battery prepared by the preparation method of the present invention has better adhesion, impedance and capacity retention rate at -10°C.

[0056] In order to further verify the optimization effect of the composite battery separator of the present invention on battery performance, a commercially available PVDF separator was used for comparison experiments with the composite battery separator of Example 2, as follows: 1. Adhesion performance test: Test the adhesion between the cold-pressed diaphragm and the positive electrode sheet. Cut the cold-pressed diaphragm and the positive electrode sheet into strips with a width of 15 mm and a length of 100 mm. The test equipment is a universal test tensile machine with a test speed of 150 mm / min and an effective test width of 15 mm. During the test, each group was sampled three times. The test results are shown in Table 2. It can be seen from Table 2 that the composite battery diaphragm of the present invention has better adhesion to the positive electrode sheet.

[0057] Table 2 Adhesion performance test results

[0058] 2. Capacity retention rate test at low temperature: The low temperature double charge test conditions are -10℃, nc constant current charging; 25℃, 1 / 3C discharge, the test results are as follows Figure 1 As shown, Figure 1 Among them, M1-7, M1-8, and M1-9 are three samples of Example 2, and B-7, B-8, and B-9 are three samples of commercially available PVDF membranes. Figure 1 It can be seen that when the composite battery separator of the present invention is applied to a lithium-ion battery, the battery capacity retention rate is significantly higher.

[0059] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite battery separator, characterized in that: It includes a diaphragm base film and a composite coating coated on at least one side of the diaphragm base film; the composite coating includes the following components: 30-60% of zeolite imidazolate framework material, 20-50% of organic-inorganic cross-linked gel precursor nanoparticles, 3-30% of aqueous binder, and 1-10% of dispersant.

2. The composite battery separator according to claim 1, characterized in that: The organic-inorganic cross-linked gel precursor nanoparticles include vinyl functionalized inorganic nanoparticles, a first monomer, a second monomer, a third monomer, an initiator, an emulsifier and a solvent, wherein the first monomer is an acrylate or allyl carbonate monomer, the second monomer is a maleimide monomer, and the third monomer is an olefin epoxy or olefin oxygen-containing heterocyclic monomer.

3. The composite battery separator according to claim 2, characterized in that: The organic-inorganic crosslinked gel precursor nanoparticles are prepared by the following steps: vinyl functionalized inorganic nanoparticles, a first monomer, a second monomer, a third monomer, an initiator and an emulsifier are uniformly mixed and dispersed in a solvent to form an emulsion system, and heated and stirred to perform emulsion polymerization to obtain organic-inorganic crosslinked gel precursor nanoparticles.

4. The composite battery separator according to claim 1, characterized in that: The zeolite imidazolate framework material is selected from at least one of ZIF-8, ZIF-67 and MOF-5.

5. The composite battery separator according to claim 1, characterized in that: The aqueous binder is selected from at least one of polyvinylidene fluoride, polyvinyl alcohol and carboxymethyl cellulose.

6. The composite battery separator according to claim 1, characterized in that: The dispersant is selected from at least one of benzalkonium chloride, polydimethylguanidine salt, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium fatty alcohol polyvinyl ether sulfate, polysorbate, sorbitan fatty acid ester, alkyl glycoside, and alkylphenol polyoxyethylene ether.

7. A method for preparing a composite battery separator, characterized in that: The steps include: (1) Preparation of organic-inorganic cross-linked gel precursor nanoparticles; (2) dispersing the zeolite imidazolate framework material, the organic-inorganic cross-linked gel precursor nanoparticles, the aqueous binder, and the dispersant in water to prepare an aqueous slurry; (3) The aqueous slurry is coated on at least one side of the separator base film by spraying or rolling, and then heated and dried to obtain a composite battery separator.

8. The preparation method according to claim 7, characterized in that: In step (3), the coating surface density of the aqueous slurry is 1-10 g / m 2 .

9. The preparation method according to claim 7, characterized in that: In step (3), the heating and drying temperature is 30-100° C., and the heating and drying time is 1-12 min.

10. A lithium ion battery, characterized in that: The invention comprises the composite battery separator according to any one of claims 1 to 6.